COVID-19 Influenced Survey on Students' Satisfaction With Psychological Acceptance Based on the Organization of Online Teaching and Learning in English - Zhang, Hua; Li, Xinguo (Frontiers in Psychology, 2022)
Due to the epidemic, many offline educational institutions and even schools have begun to seek new teaching methods, and online teaching has become an important teaching method in this situation. Online teaching refers to the teaching mode in which teachers teach online through the Internet and students learn in online classrooms. Online teaching can reduce crowd contact between students and prevent the spread of the epidemic. However, due to the virtual nature of the Internet and the immaturity of the online teaching system, the current online teaching method cannot be accepted by the majority of teachers and students. Therefore, this paper conducts a satisfaction survey on the psychological acceptance ability of students under the online teaching organization of English majors, aiming to understand the actual psychological burden brought by online teaching to students. The content of the questionnaire includes students' satisfaction with courses and teaching, satisfaction with teacher-student interaction, satisfaction with platforms and resources, satisfaction with teaching performance, and overall satisfaction. The survey results show that students' satisfaction with courses is generally above 4 points, while their satisfaction with teaching is generally lower, ranging from 3.65 to 3.94 points. Students' satisfaction with teacher-student interaction is not very high, around 3.75. Students' satisfaction with the teaching platform is higher than that of teachers, with a score of 4.05 or more. In terms of students' satisfaction with teaching performance, male students' satisfaction is above 4.45 points, while female students' satisfaction is 4.35 points. For overall satisfaction, male students scored above 4.45, while female students scored 4.35. Since the satisfaction in all aspects is h